Integration of Lecture and Role-Play in Teaching Immunology to Medical Students - Behrooz Pouragha; Zohreh Ghazivakili; Roohangiz Norouzinia; Nafiseh Pakravan (Kerman University of Medical Sciences, 2019)
Background Medical education is viewed as a challenging phenomenon, which can cause stress in learners and affect the learning quality. Considering the importance of basic sciences education, development of new pedagogical approaches is necessary to improve medical education. Role-play is an efficient simulation-based approach, which can improve the students' perception and imagination. In basic sciences, immunology is of high relevance in clinical situations, as immunological disorders are becoming increasingly prevalent. Objectives Given the importance of deep learning in immunology, we integrated role-play in teaching immunology to medical students in order to promote deep and durable learning. Methods In this study, two independent classes of medical students were evaluated in two consecutive academic semesters in 2014 - 2015. In one class, only lectures were conducted, while in the other class, lectures, along with role-play, were integrated. Pretest and posttest scores were determined at the beginning and end of the semesters in both classes, and the scores were compared. Also, the students' point of view was studied using a questionnaire. Results The pretest score, which indicated the students' general knowledge of immunology, was not significantly different between the two classes. However, there was an increase in the score of students participating in the class, which integrated lecture and role-play. In addition, the score obtained by female students, who participated in the class with lecture and role-play, was significantly higher than that of female students in the lecture-based class. The results of the questionnaire revealed that the students were satisfied with the integrated teaching method and believed that their knowledge had improved. Conclusions Based on the findings, dramatization can make learning an exciting process and improve the students' understanding of immunology concepts.